THE EFFECT OF DENSITY AND FLOOR TYPES ON PERFORMANCE, PHYSIOLOGICAL STATE AND IMMUNE RESPONSE OF BROILERS - Sunarti, D.; Haryono, H.; Soedarsono, S. (Journal of the Indonesian Tropical Animal Agriculture, 2010)
The purpose of this research was to study the effect of density and floor types on performance,physiological state and immune response of broilers. The research involved 368 male broilers of theNew Lohman strain aged 8 days which were raised up to 35 days at different densities and floor types.Floor types consisted of rice hull litter and bamboo slat were used as the main plot; while densities of 7,10, 13 and 16 birds/m2 applied as the sub-plot. The results showed that the final body weight gain of the35-day Lohmann broilers at densities of 7, 10 and 13 birds/m2 were 28.22, 24.43 and 19.27 kgrespectively, compared to 16 birds/m2 at 13.53 kg (P>0.05). Broilers in the bamboo slats floor hadlymph weight at 3.73 g compared to the litter floor at 2.55 g (P<0.05). Also, broilers in the bambooslats had average RHL (0.65) lower than broilers in the litter floor (0.79). It could be concluded thatbamboo slats best being used for broilers up to a density of 13 broilers/m2.